2020
DOI: 10.3390/nu12010229
|View full text |Cite
|
Sign up to set email alerts
|

Sharing is Caring: A Study of Food-Sharing Practices in Australian Early Childhood Education and Care Services

Abstract: Food connects people, and can significantly impact the physical, social and emotional development of young children. Food sharing and family-style mealtimes can support healthy eating practices and psychological well-being among young children, and carersother than family members, such as Early Childhood Education and Care staff, play an important role in the provision of these practices. Despite increasing numbers of Australian children attending Early Childhood Education and Care services, there is often rel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 49 publications
0
4
0
Order By: Relevance
“…Despite differences in the oral processing time between young and elderly people [ 20 ], nutritional supplementation is possible without chewing. Thus, the importance of food education from early childhood has been demonstrated in recent years [ 21 ]. In general, the effects of food form on cognitive function have already been examined [ 22 , 23 , 24 ].…”
Section: Introductionmentioning
confidence: 99%
“…Despite differences in the oral processing time between young and elderly people [ 20 ], nutritional supplementation is possible without chewing. Thus, the importance of food education from early childhood has been demonstrated in recent years [ 21 ]. In general, the effects of food form on cognitive function have already been examined [ 22 , 23 , 24 ].…”
Section: Introductionmentioning
confidence: 99%
“…Five studies focused exclusively on grandparents [ 33 , 38 , 42 , 44 , 57 ]. Seven studies focused exclusively on formally employed child care workers [ 30 , 34 , 36 , 46 , 56 , 58 , 61 ]. One study focused on students in training to become child care workers [ 49 ].…”
Section: Resultsmentioning
confidence: 99%
“…This finding was salient in the case of child care workers. Vandeweghe et al [ 59 , 60 ] and Wallace et al [ 61 ] showed how NMCs cannot enact some supportive feeding practices because they do not control all of the decisions in and conditions of the caregiving setting. Furthermore, Love et al [ 49 ] found that child care workers must consider parental wishes even if they are inconsistent with center policy.…”
Section: Discussionmentioning
confidence: 99%
“…However, today, a new wave of childhood studies blends both biological and social paradigms (Ryan, 2012). The definition of health is now growing to encompass not only physical health but also emotional, social, and spiritual wellbeing in young children (Wallace et al, 2020). Not only is the consumption of food a main source of sociality (Bellah, 2005), sharing food in an early childhood classroom can even be a form of everyday spirituality (Bone, 2005).…”
Section: Sociocultural Perspectivesmentioning
confidence: 99%